Ultimate visual dictionary - Dorling Kindersley Publishing, Inc. (New York : Dorling Kindersley, 2000)
Discover the definitions you need with this small dictionary that uses pictures, diagrams, and detailed annotations.
Keywords: Picture dictionaries, English; English language